Diskriminasi Keagamaan dan Kebudayaan Terhadap Masyarakat Digital: Religious and Cultural Discrimination against Digital Society - Windar; Abd Wahidin; Abd Rasyid (IAIN Parepare, 2023)
Discrimination is a behavior that is very unifair and unequal to what is done in distinguishing individuals or groups, based on something, usually categorical or specific, such as race, ethnicity, social classes and even religion. As time goes by, developments in various parts of the world are increasingly sophisticated, especially ini Indonesia itself, various advences have now increased. Developments in the digital are are one of the advancements that have developed rapidly in Indonesia. In today’s development, it has now spread to social media. In Indonesia itself, many and even millions of people use social media as a place to spread information. It can even be used to get new information from various sources that have been shared by the public. In Indonesia itself there is a variety of diversity so that Indonesia is dubbed as a multicultural country, the diversity referrd to is the devesity of ethnicities, races, customs, culture and religion. The existence of these differences will not lead to conflict and even discrimination against certain groups, it is the existence of these differences that triggers discrimination because everyone has different understanding of something so that it becomes big. This is because until now there is still a lot of violence and discrimination against certain groups in society, this is what will lead to social conflicts that will be even more acute in the multidimensional crisis that is happening in Indonesia. Especially in a digital society where they use digital media tools to find information. and even use digital media as a tool to discriminate against these community groups